Late Antique Changes in the Urban Structure of the Dalmatian Metropolis - the Episcopal Complex in Salona - Maraković, Nikolina (Array, 2012)
The authors are bringing forth new interpretations of the old finds in the area of the Episcopal complex in Salona, revising the chronology of its development.